2015
DOI: 10.1186/s12944-015-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the beta-3 adrenergic receptor Trp64Arg and uncoupling protein 1–3826 A > G genotypes on lipid and apolipoprotein levels in overweight/obese and non-obese Chinese subjects

Abstract: BackgroundThe beta-3 adrenergic receptor (β3-AR) Trp64Arg and uncoupling protein 1 (UCP1) -3826 A > G polymorphisms have been reported to be associated with obesity and/or lipid metabolism in some populations. This study examined the possible association of the β3-AR and UCP1 polymorphisms with overweight/obesity or lipid variation in a Southwest Chinese population.MethodsA total of 418 Han Chinese (249 overweight/obese and 169 healthy control subjects) in the Chengdu area were studied using PCR-RFLP analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Williams and Thompson showed that walking and running decrease the risk of development of hypercholesterolaemia in an equally effective manner [7]. The results by Marigliano et al are in concordance with the data of the above discussed studies and demonstrate considerable positive effect of walking on lipid metabolism parameters [8]. At the same time, meta-analysis presented in 2018 by Oja et al failed to demonstrate the direct effect of walking on cholesterol, while its essential effect on body mass index (BMI) and blood pressure parameters was proven [9].…”
Section: Introductionsupporting
confidence: 59%
“…Williams and Thompson showed that walking and running decrease the risk of development of hypercholesterolaemia in an equally effective manner [7]. The results by Marigliano et al are in concordance with the data of the above discussed studies and demonstrate considerable positive effect of walking on lipid metabolism parameters [8]. At the same time, meta-analysis presented in 2018 by Oja et al failed to demonstrate the direct effect of walking on cholesterol, while its essential effect on body mass index (BMI) and blood pressure parameters was proven [9].…”
Section: Introductionsupporting
confidence: 59%
“…Recently, BAT has been identi ed as a novel target of obesity, as it increases energy expenditure by non-shivering thermogenesis. BAT-related gene polymorphisms are associated with obesity (8)(9)(10)(11). However, these relationships have not yet been fully elucidated, especially in pediatric obesity.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are key molecules in BAT thermogenesis. In fact, some studies have demonstrated that these genes are associated with the pathogenesis of adulthood obesity (8)(9)(10)(11). However, few studies have reported the association between these genes and pediatric obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Those pathological stimuli trigger further a cascade of pathological events in cells although some studies proposed those stimuli as the group of cardioprotective signaling molecules, mainly in pre-and post-conditioning processes. Interestingly, some early and recent studies, particularly obesity studies in animals, highlighted an important anti-obesity and anti-diabetic effect of some selective beta-3 adrenergic receptor (β 3 -AR) agonists [94][95][96][97][98]. Indeed, some studies summarized the beneficial effects of some β 3 -AR agonists for the treatment of diabetes and obesity as increase lipolysis, fat oxidation, energy expenditure, and insulin action.…”
Section: New Therapeutic Agents In Obesity-related Cardiovascular Disordersmentioning
confidence: 99%